Costituzione e intelligenza artificiale: un’agenda per il prossimo futuro (TEST BioLaw Journal - Rivista di BioDiritto, 2019)
The Italian Constitution was written in 1946 and 1947, when the Turing test was not even developed. Yet, a number of principles contained in it can be effectively applied in order to obtain a human-centered Artificial Intelligence. This article deals with a few constitutional principles (democracy, sovereignty, equality, etc.) in order to identify new rights (such as the right to know about the rationale behind the AI decision, the right to know about the artificial or human nature of the entity I am talking with, the right to a decision not based only on automated processing) that can make AI a valuable resource – and not a threat – for individuals and the community.
Keywords: Artificial Intelligence; Constitutional law; fundamental rights; human-centered AI